دور الشرطة المجتمعية في تعزيز الوعي الاجتماعي والوقاية من الإشاعة - الجازي، علي سويلم مهنا (مديرية الأمن العام - أكاديمية الشرطة الملكية, 2019)
هدفت الدراسة التعرف إلى دور الشرطة المجتمعية في تعزيز الوعي الاجتماعي والوقاية من الإشاعة، من أجل تحقيق أهداف الدراسة تم استخدم المنهج الوصفي التحليلي كمنهج للمعالجة للوقوف على الجوانب الأساسية للدراسة، ولتقديم التطبيقات المعاصرة والقديمة في سياق هذه الأسس العلمية. وقد توصلت الدراسة إلى مجموعة من النتائج كان أهمها: أن الشرطة المجتمعية ساهمت في خلق بيئة آمنة في المناطق، كما أنها ساهمت في التطبيق الأمثل للقانون، بالإضافة إلى أن الشرطة المجتمعية ساهمت في تحقيق مبدأ الشراكة الفاعلة مع المواطنين والوقاية من الإشاعات، كذلك يوجد دور للشرطة المجتمعية في تعزيز الوعي المجتمعي والوقاية من الإشاعة. قدمت الدراسة مجموعه من التوصيات منها: ضرورة زيادة مساهمة الشرطة المجتمعية في تحقيق مقومات الأمن الاجتماعي من خلال زيادة البرامج التوعوية والمحاضرات التثقيفية، وتقديم المساعدات الإنسانية بالإضافة إلى بناء جسور الثقة الحقيقية مع المواطنين لتقليص الهوة بينهم وبين رجال الشرطة من أجل كشف الحقائق ومحاربة مروجي الإشاعات. The study aimed to identify the role of community police in promoting community awareness and prevention of rumor. In order to achieve the objectives of the study was used descriptive analytical approach as a treatment approach to identify the basic aspects of the study, and to provide contemporary and ancient applications in the context of these scientific foundations. The study reached a number of results, the most important of which were: The community police have contributed to the creation of a safe environment in the areas, and contributed to the optimal application of the law, in addition to the community police contributed to the realization of the principle of effective partnership with citizens and the prevention of rumors, as well as the role of community police in promoting community awareness and prevention of rumor. The study submitted a number of recommendations, including: The need to increase the contribution of community police to achieve the elements of social security through increased awareness programs and educational lectures, and the provision of humanitarian assistance in addition to building bridges of trust with citizens to reduce the gap between them and the police in order to uncover the facts and fight rumors.
Keywords: الشرطة المجتمعية -- الوعي المجتمعي -- الأمان الاجتماعي -- المساعدات الإنسانية